High-intensity aerobic exercise training improves exercise capacity, dyspnea, and fatigue in patients with severe asthma using triple inhaler - Lun-Yu Jao; Po-Chun Hsieh; Yao-Kuang Wu; I-Shiang Tzeng; Mei-Chen Yang; Wen-Lin Su; Chou-Chin Lan (Tzu Chi Medical Journal)
Objectives: Asthma is a chronic respiratory disease that affects millions of people worldwide and causes severe symptoms such as wheezing, coughing, and breathing difficulty. Despite modern treatments, 3%–10% of patients develop severe asthma, which requires high-dose medications, and they may still experience frequent and severe symptoms, exacerbations, and psychological impacts. This study aimed to investigate the effects of high-intensity aerobic exercise training (HIAET) in patients with severe asthma. Materials and Methods: Patients with severe asthma were recruited, and cardiopulmonary exercise tests, dyspnea, and leg fatigue scores were performed before HIAET. Participants underwent a 12-week hospital-based HIAET, which involved exercising twice weekly to reach 80% of their peak oxygen uptake (VO2). Results: Eighteen patients with severe asthma underwent HIAET, which resulted in significant improvement in peak VO2 (1214.0 ± 297.9–1349.4 ± 311.2 mL/min, P = 0.004) and work rate (80.6 ± 21.2–96.2 ± 24.8 watt, P < 0.001) and decrease in dyspnea (5.1 ± 1.8–4.1 ± 1.2, P = 0.017) and fatigue scores (5.2 ± 2.3–4.0 ± 1.2, P = 0.020) at peak exercise. No significant changes were observed in spirometry results, respiratory muscle strength, or circulatory parameters. Conclusion: HIAET can lead to improved exercise capacity and reduced dyspnea and fatigue scores at peak exercise without changes in spirometry, respiratory muscle strength, and circulatory parameters.